-57=6p-9

Simple and best practice solution for -57=6p-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -57=6p-9 equation:



-57=6p-9
We move all terms to the left:
-57-(6p-9)=0
We get rid of parentheses
-6p+9-57=0
We add all the numbers together, and all the variables
-6p-48=0
We move all terms containing p to the left, all other terms to the right
-6p=48
p=48/-6
p=-8

See similar equations:

| (2/3)x+6=14 | | v/3+1=7 | | b-1+5=24 | | -8x+6=9x-9 | | (5s+8)/7=4 | | 15w+11=1+15w+10 | | 3r=5r−10 | | -2(x-1)-2x=4-4(x+2) | | 12x-14+8x=20 | | 16/2x=2^-1 | | |5x−25|=15 | | 7x-(3x-8)=7+2(4x-5) | | x^2-3x-62=0 | | 9(y-4)=36 | | 2(2y-1)=12 | | -2x+8=4.53 | | 7m-3-3(m+1)=-(7m-4) | | 15y+7=-20y | | 2(3x-3)=4(x+3) | | 7m-3-3(m+1)=-(7m+4) | | 90x=-3 | | 12x-5=110x | | 6^3x+4=36^2x-3 | | (8x)/3=2x+6 | | -9y+(8=27 | | 45-5x=2 | | 3x+4/2=6.5 | | 20x2-7x-6=0 | | (x-1)(x+1)*x*(x+2)=24 | | (x-1)*(x+1)x(x+2)=24 | | 3x+4/3=6.5 | | x+.05x=135 |

Equations solver categories